Recent Advances in Nano-Therapeutic Strategies for Osteoarthritis - Guo, Xinjing; Lou, Jia; Wang, Fazhan; Fan, Daoyang; Qin, Zhihai (Frontiers in Pharmacology, 2022)
Osteoarthritis (OA) is the most common type of arthritis and the leading cause of disability globally. It tends to occur in middle age or due to an injury or obesity. OA occurs with the onset of symptoms, including joint swelling, joint effusion, and limited movement at a late stage of the disease, which leads to teratogenesis and loss of joint function. During the pathogenesis of this degenerative joint lesion, several local inflammatory responses are activated, resulting in synovial proliferation and pannus formation that facilitates the destruction of the bone and the articular cartilage. The commonly used drugs for the clinical diagnosis and treatment of OA have limitations such as low bioavailability, short half-life, poor targeting, and high systemic toxicity. With the application of nanomaterials and intelligent nanomedicines, novel nanotherapeutic strategies have shown more specific targeting, prolonged half-life, refined bioavailability, and reduced systemic toxicity, compared to the existing medications. In this review, we summarized the recent advancements in new nanotherapeutic strategies for OA and provided suggestions for improving the treatment of OA.